PELATIHAN APLIKASI ZOOM MEETING SEBAGAI LAYANAN KONFERENSI DALAM MEDIA PEMBELAJARAN JARAK JAUH DI SD NEGERI AJIBAHO - Adrial Falahi; Julianto Hutasuhut (PKM Maju UDA, 2021)
This community service (PKM) aims to improve the knowledge and skills of teachers in utilizing remote conferencing services with a combination of video, online meetings and in-app chat in the form of "Zoom Cloud Meeting". With this PKM, it is hoped that teachers and students who take part in this program can use it in the learning process in the midst of a pandemic that was carried out at SD Negeri 101809 Ajibaho, Sibiru-Biru District, Deli Serdang Regency, North Sumatra Province. The number of participants involved in this PKM is 13 teachers and students. The method used in this service is to provide education and training to partners by utilizing each of the communication devices they have. Technical training is carried out alternately in running the Zoom application either as an admin or operator or as a participant with direct guidance. When this service was carried out, previously most of the participants were only able to run applications by acting as participants whose level of ability to operate the application was very simple and only 20% were able to operate as operators, but after this service the teachers have been able to run applications by acting as operators. with a higher difficulty level of 80%. This shows that most teachers are able to organize distance learning (online) based on video conferencing. So with this PKM, teachers are better able to use the Zoom application by shifting roles that were previously only able to be participants after participating in this PKM program, they are already able to become operators.